Community Engagement and Capacity-Building needs in Technology Intervention - Rauniyar, A.; Shrestha, Shisher (International Water Management Institute, 2024)
Climate change is having a global impact on water security and agricultural practices. As a result, there is a need for sustainable agricultural practices (Singh et al., 2024). Boosting agriculture in a changing climate requires climate-resilient technologies that address both adaptation and mitigation measures. Solar irrigation systems offer a promising solution by providing an environmentally friendly and cost-effective alternative to traditional diesel-powered irrigation pumps (Li et al., 2017). However, the successful implementation of these systems relies heavily on field-based comprehensive capacity building of the end users. Unlike conventional training, which often focuses on immediate skill acquisition, capacity-building through interactive community engagement aims to foster long-term sustainability and resilience (Anthony, 2024).